Increased Intestinal Inflammation and Permeability in Glaucoma - Wang Z; Guo S; He C; Chen L; Wang J; Xiu W; Zhang G; Chen Y; Li A; Zhu X; Xiao X; Yu L; et al. (Dove Medical Press, 2024)
Zuo Wang,1,2,* Siqi Guo,3,* Chong He,2,4,* Lingling Chen,5 Jinxia Wang,2 Wenbo Xiu,2 Gao Zhang,2 Yang Chen,2 An Li,2 Xiong Zhu,6 Xiao Xiao,2 Ling Yu,3 Fang Lu2,4,7 1Department of Clinical Laboratory, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, Affiliated Cancer Hospital of University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 2Clinical Immunology Translational Medicine Key Laboratory of Sichuan Province, Sichuan Provincial People's Hospital, University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 3Department of Ophthalmology, Daping Hospital, Army Medical Center, Army Medical University, Chongqing, People's Republic of China; 4Medico-Engineering Cooperation on Applied Medicine Research Center, University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 5Department of Immunology, West China School of Basic Medical Sciences & Forensic Medicine, Sichuan University, Chengdu, People's Republic of China; 6Department of Prenatal Diagnosis, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 7Health Management Center, Sichuan Provincial People's Hospital, University of Electronic Science and Technology of China, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Ling Yu; Fang Lu, Email oculistlingyu@hotmail.com; lufangfang@126.comObjective: Evidence suggests that dysbiosis of the gut microbiota plays a pivotal role in the development of glaucoma. This dysbiosis is commonly associated with chronic intestinal inflammation and increased intestinal permeability. However, the understanding of intestinal inflammation and permeability in glaucoma remains insufficient. This study aims to investigate the potential relationship between fecal inflammation and permeability markers and glaucoma.Methods: We recruited 114 glaucoma patients and 75 healthy controls. Levels of fecal lactoferrin (Lf) and alpha-1 antitrypsin (AAT) were quantified using enzyme linked immunosorbent assay (ELISA) to compare both biomarkers between groups and across different severity grades of glaucoma. Logistic regression analysis was used to assess the association between these fecal biomarkers and glaucoma. The severity of glaucoma was assessed based on the mean deviation (MD) in the visual field.Results: In this study, we observed elevated levels of fecal Lf and AAT in glaucoma patients. The proportion of glaucoma patients with abnormal fecal Lf levels (≥ 7.25 μg/g) was significantly higher than that of the controls (p = 0.012). A positive correlation was noted between fecal Lf and AAT (rho = 0.20, p = 0.006). After adjusting for age and sex, multivariable logistic regression analysis indicated that both fecal Lf (OR = 1.11, 95% CI: 1.01- 1.21, p = 0.026) and AAT (OR = 1.01, 95% CI: 1.01- 1.02, p < 0.001) positively correlated with glaucoma. These biomarkers might reflect glaucoma severity, with significant differences in fecal Lf levels observed between moderate and severe stages, but not in the early stage. Furthermore, increasing levels of fecal AAT correlated with greater severity of glaucomatous injury and a larger vertical cup-to-disc ratio (VCDR) (p < 0.05).Conclusion: This study suggests an increase in intestinal inflammation and permeability in glaucoma, further indicating the importance of the 'gut-retina axis' in the pathogenesis of the disease and potentially offering new therapeutic avenues.Keywords: fecal lactoferrin, fecal alpha-1 antitrypsin, glaucoma, intestinal inflammation, intestinal permeability, intestinal barrier